Off-campus students receive food donation from YaPEIM and UMP - Nor Salwana, Mohammad Idris (2020)
Pekan, 15 October 2020 - A total of 200 Universiti Malaysia Pahang (UMP) students who live off-campus and cannot return to their hometowns received food donations in the Foodbank 2.0 programme organised by the Malaysian Islamic Economic Development Foundation (YaPEIM).